Analysis of MHD on Convective Mass Transfer in Annular Flow: Catheter-Based Drug Delivery Systems - Punith Kumar Deshapande; Indira Rama Rao; Sravan Kumar Thavada (Mathematics and Computer Science: Contemporary Developments Vol. 10, 2024)
A catheter is a tube that can be inserted into a body cavity, duct, or vessel. It is a thin, flexible tube. A catheter left inside the body either temporarily or permanently is referred to as an indwelling catheter. In the present study, convective diffusive mass transfer is considered, along with the effects of particle drag under the influence of a magnetic field concerning drug delivery in the presence of the catheter. A concentric annular region is created by the presence of a catheter, and the effects of which on mass transfer are considered. A model of the hydrodynamics of the fluid, blood flow, and convective diffusive mass transfer of the species is presented. Here, an attempt is made to analyze a drug delivery method for delivering a drug to a specific site in the body and for this analysis, considered a channel bounded by the tissue region where the drug is targeted. The magnetic field induces pulsatile flow, which affects the mass transfer. The graphs predict that the mass transfer increases from the lumen region to the tissue region. Peclet number and magnetic parameter are the parameters that significantly affect carrying drugs towards the tissue. The results are well agreed with the physical phenomena of the problem as well as many biomedical applications. The study concluded that the diffusion coefficient increases with an increase in permeability due to enhancement in convection of fluid towards the wall thereby increasing absorption. Peclet number and magnetic field influence diffusion significantly. The effect of an increase in a magnetic field is to create pulsatile motion.